2014
DOI: 10.1002/aqc.2465
|View full text |Cite
|
Sign up to set email alerts
|

Changes in habitat use patterns by bottlenose dolphins over a 10‐year period render static management boundaries ineffective

Abstract: Bottlenose dolphins (Tursiops truncatus) in northern New Zealand range widely and their coastal distribution increases their risk of exposure to a variety of threats. Marine protected areas (MPAs) are increasingly used to protect species but there is a paucity of studies examining their efficacy. In the Bay of Islands, New Zealand (35°14'S, 174°06'E), dolphin distribution and habitat use patterns were examined between two time periods: 1996–2000 and 2007–2010. In addition, dolphin use of tourism exclusion zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 54 publications
1
33
1
Order By: Relevance
“…Dolphins in the Bay of Islands have changed their patterns of residency and habitat use over time, with an apparent shift in home range (Tezanos‐Pinto , Hartel et al . ). In a stable population that had not undergone a shift in home range, it would be expected that all calves would have equal survival probabilities.…”
Section: Methodsmentioning
confidence: 97%
“…Dolphins in the Bay of Islands have changed their patterns of residency and habitat use over time, with an apparent shift in home range (Tezanos‐Pinto , Hartel et al . ). In a stable population that had not undergone a shift in home range, it would be expected that all calves would have equal survival probabilities.…”
Section: Methodsmentioning
confidence: 97%
“…Mann et al (2000) found bottlenose dolphin group sizes were largest for groups with calves up to 3 mo old, which may also in part explain the formation of large groups at GBI given the high frequency of neonates and calves recorded. Based on the variable patterns of site fidelity and habitat use observed in BOI (Constantine 2002, Tezanos-Pinto 2009, Hartel et al 2014, Tezanos-Pinto et al 2013, we anticipated new individuals would continue to be photo-identified for the duration of the study. The discovery curve reached a plateau after 17 mo of field effort, although a further 8 new individuals were added to the catalogue in the final summer season.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the species in this region has primarily been driven by funding generated from dolphin tourism levies through the Department of Conservation (DOC), the government agency responsible for managing New Zealand's marine mammal species (e.g. Constantine & Baker 1997, Constantine et al 2003, Hartel et al 2014). As such, research on this population has not only been heavily focused on tourism effects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Such long-term stability in habitat use is important when considering spatially explicit conservation measures, such as marine protected areas (Hartel, Constantine, & Torres, 2015;Wilson, Reid, Grellier, Thompson, & Hammond, 2004). The observed species-environment relationships and resulting habitat use patterns for both species remained stable over a decade.…”
Section: Conservation Implicationsmentioning
confidence: 97%